2016
DOI: 10.1186/s40064-016-3442-4
|View full text |Cite
|
Sign up to set email alerts
|

Urdu Nasta’liq text recognition using implicit segmentation based on multi-dimensional long short term memory neural networks

Abstract: The recognition of Arabic script and its derivatives such as Urdu, Persian, Pashto etc. is a difficult task due to complexity of this script. Particularly, Urdu text recognition is more difficult due to its Nasta’liq writing style. Nasta’liq writing style inherits complex calligraphic nature, which presents major issues to recognition of Urdu text owing to diagonality in writing, high cursiveness, context sensitivity and overlapping of characters. Therefore, the work done for recognition of Arabic script canno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 28 publications
0
23
0
Order By: Relevance
“…In some cases, the main body and dots are separately recognized [127] to reduce the total number of unique classes which can be very high (Urdu, for example, has more than 26,000 unique ligatures [128]). The implicit segmentationbased recognition techniques mostly employ different variants of LSTMs [121,129,130] with a connectionist temporal classification (CTC) output layer to recognize characters. A significant proportion of studies targeting recognition of Urdu text employ the publicly available UPTI [131] and CLE [132] datasets.…”
Section: Text Recognitionmentioning
confidence: 99%
“…In some cases, the main body and dots are separately recognized [127] to reduce the total number of unique classes which can be very high (Urdu, for example, has more than 26,000 unique ligatures [128]). The implicit segmentationbased recognition techniques mostly employ different variants of LSTMs [121,129,130] with a connectionist temporal classification (CTC) output layer to recognize characters. A significant proportion of studies targeting recognition of Urdu text employ the publicly available UPTI [131] and CLE [132] datasets.…”
Section: Text Recognitionmentioning
confidence: 99%
“…It is suitable for context learning applications. It has been applied on various research tasks in document image analysis specifically relevant to cursive script as reported in [3]- [5] and [9]. The proposed system is investigated by multidimensional LSTM networks because it maintains contextual information and temporarily correlates the new sequences with previous one.…”
Section: B Mdlstm Network Training For Arabic Scene Textmentioning
confidence: 99%
“…The field of text analysis in camera captured images constitute a considerable challenge to address by research community. The work presented in recent years, mostly converged on correct detection of text area in presence of other objects in an image [1], [3], [5]. The scene text can be categorized as a typical OCR problem after text detection and segmentation.…”
Section: Introductionmentioning
confidence: 99%
“…The multi-dimensional long short term memory recurrent neural network (MDLSTM RNN) with connectionist temporal classification (CTC) as output layer gives 96.40% Urdu character recognition accuracy tested on 1600 text line images UPTI [27]. The character recognition accuracy is further improved by using a MDLSTM RNN with a matured output layer for sequence labeling giving 98% character recognition accuracy tested on UPTI dataset [28]. The hand crafted features are extracted using Convolutional Neural Networks (CNN) which are fed to MDLSTM for Urdu characters training and recognition.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In Figure 6, AIEN character has different shapes at isolated and final positions. The same character labels of different shapes of a character as presented in [26]- [28] may generate confusions during recognition. However, it is the strength of the sequence learning approach which performs well for the recognition of Nastalique text lines having same labels of multiple contextual character shapes.…”
Section: Literature Reviewmentioning
confidence: 99%